ErbB2 Targeted Epigenetic Modulation: Anti-tumor Efficacy of the ADC Trastuzumab-HDACi ST8176AA1 - Milazzo, Ferdinando Maria; Vesci, Loredana; Anastasi, Anna Maria; Chiapparino, Caterina; Rosi, Antonio; Giannini, Giuseppe; Taddei, Maurizio; Cini, Elena; Faltoni, Valentina; Petricci, Elena; Battistuzzi, Gianfranco; Salvini, Laura; et al. (Frontiers in Oncology, 2020)
Targeted therapy using monoclonal antibodies conjugated to toxins is gaining space in the treatment of cancer. Here, we report the antitumor effect of a new antibody drug conjugate (ADC) delivering a HDAC inhibitor to ErbB2+ solid tumors. Trastuzumab was partially reduced with tris [2-carboxyethyl] phosphine (TCEP) and conjugated to ST7464AA1, the active form of the prodrug HDAC inhibitor ST7612AA1, through a maleimide-thiol linker to obtain the Antibody Drug Conjugate (ADC) ST8176AA1. The average drug/antibody ratio (DAR) was 4.5 as measured by hydrophobic interaction chromatography (HIC). Binding of ST8176AA1 to ErbB2 receptor and internalization in tumor cells were investigated by enzyme-linked immunosorbent assay (ELISA), surface plasmon resonance (SPR), cytofluorimetry and High Content Screening (HCS) Imaging. The biological activity of the ADC was evaluated in vitro and in vivo by measuring cell proliferation/cell cycle, apoptosis/DNA damage, tubulin and histone acetylation and modulation of Epithelial/Mesenchymal Transition (EMT) markers. Receptor binding and internalization of ST8176AA1 were confirmed to be similar to trastuzumab. Higher anti-tumor activity of ST8176AA1 compared to trastuzumab was observed in vitro in tumor cell lines. Such higher activity correlated with increased acetylation of histones and alfa-tubulin as a consequence of HDAC inhibitor-mediated epigenetic modulation that also induced increased expression of ErbB2 and estrogen receptor in triple negative breast cancer cells. Consistently with in vitro data, ST8176AA1 exhibited higher tumor growth inhibition than trastuzumab in xenograft models of ovary and colon carcinoma and in two patient-derived (PDX) models of pancreatic carcinoma. Immunohistochemistry analysis of tumor masses showed lower expression of the proliferation marker Ki67 and higher expression of cleaved caspase-3 in mice treated with the ADC compared to those treated with trastuzumab and results correlated with increased acetylation of both histones and tubulin. Collectively, present data indicate that ADC ST8176AA1 can target epigenetic modulation to ErbB2+ tumors. Interestingly, the amount of HDACi estimated to be delivered at the ST8176AA1 effective dose would correspond to approximately 1/1000 of ST7612AA1 effective dose. Therefore, ST8176AA1 is an attractive new therapeutic candidate because it exhibits increased anti-tumor potency compared to trastuzumab by exerting epigenetic modulation at a much safer dose compared to standard HDACi-based therapeutic protocols.